Context-Aware Software Variability through Adaptable Interpreters - Cazzola, Walter; Shaqiri, Albert (IEEE software, 2017)
A proposed approach moves variability support from the programming language to the language implementation level. This enables contextual variability in any application independently of whether the underlying language supports context-oriented programming. A Neverlang-based prototype implementation illustrates this approach.